2023
DOI: 10.18632/aging.205190
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic quantification of native and ECM-enriched mouse ovaries reveals an age-dependent fibro-inflammatory signature

Shweta S. Dipali,
Christina D. King,
Jacob P. Rose
et al.

Abstract: The ovarian microenvironment becomes fibrotic and stiff with age, in part due to increased collagen and decreased hyaluronan. However, the extracellular matrix (ECM) is a complex network of hundreds of proteins, glycoproteins, and glycans which are highly tissue specific and undergo pronounced changes with age. To obtain an unbiased and comprehensive profile of age-associated alterations to the murine ovarian proteome and ECM, we used a label-free quantitative proteomic methodology. We validated conditions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 94 publications
(160 reference statements)
0
0
0
Order By: Relevance
“…Pro-inflammatory cytokine (IL-6, IL-1β, IL-8, interferon-γ [Infg], TNF-α) and chemokine (monocyte chemoattractant protein-1 [Ccl2], C-C motif chemokine ligand [Ccl] 5, and C-X-C motif chemokine ligand [Cxcl] 2) levels also increase within the aged ovary (Briley et al, 2016, Lliberos et al, 2021, Umehara et al, 2022. A recent proteomics study in murine ovary also demonstrated an age-related increase in several markers of pro-inflammatory stress and immune responses, suggesting increased chemotaxis and lymphocyte-mediated immunity (Dipali et al, 2023). Although the contributions of individual ovarian cell types and immune cells to these phenotypic changes remain unclear, the overall changes are aligned with what is reported in a recent single-cell transcriptomic and FACS analyses (Isola et al, 2024).…”
Section: Age-related Pro-inflammatory Stress In the Ovarymentioning
confidence: 99%
See 2 more Smart Citations
“…Pro-inflammatory cytokine (IL-6, IL-1β, IL-8, interferon-γ [Infg], TNF-α) and chemokine (monocyte chemoattractant protein-1 [Ccl2], C-C motif chemokine ligand [Ccl] 5, and C-X-C motif chemokine ligand [Cxcl] 2) levels also increase within the aged ovary (Briley et al, 2016, Lliberos et al, 2021, Umehara et al, 2022. A recent proteomics study in murine ovary also demonstrated an age-related increase in several markers of pro-inflammatory stress and immune responses, suggesting increased chemotaxis and lymphocyte-mediated immunity (Dipali et al, 2023). Although the contributions of individual ovarian cell types and immune cells to these phenotypic changes remain unclear, the overall changes are aligned with what is reported in a recent single-cell transcriptomic and FACS analyses (Isola et al, 2024).…”
Section: Age-related Pro-inflammatory Stress In the Ovarymentioning
confidence: 99%
“…For instance, transforming growth factor-β (TGF-β) signaling is important for theca and granulosa cell communication during follicular growth (Knight and Glister, 2006) and also provoked during aging. Enhanced TGF-β activity has been linked to lymphocyte chemotaxis and activation (McCloskey et al, 2020, Li et al, 2006, which increases in the aging ovary (Dipali et al, 2023, Isola et al, 2024. Moreover, TGF-β activity plays a well-established role in driving collagen accumulation and fibrosis during aging (Ren et al, 2023).…”
Section: Age-related Pro-inflammatory Stress In the Ovarymentioning
confidence: 99%
See 1 more Smart Citation
“…With age, mouse ovaries exhibit increased expression of pro-inflammatory molecules as well as the presence of a unique immune cell population associated with chronic inflammation [ 13 , 15 , 16 , 19 ]. Moreover, ovaries from reproductively old mice contain high levels of collagen I and III, are enriched in fibro-inflammatory proteins, and have reduced hyaluronan content [ 11 , 13 , 24 , 25 ] Many of these phenotypes are conserved in the human ovary as well [ 26 , 27 ]. This age-dependent increase in ovarian fibrosis is directly associated with increased ovarian stiffness [ 24 ].…”
Section: Introductionmentioning
confidence: 99%